2020
DOI: 10.3389/fneur.2020.00097
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Stenting After Failed Thrombectomy in Patients With Moderately Severe Stroke: A Multicenter Cohort Study

Abstract: Results: Forty-one patients met the inclusion criteria. A median of 2 retrievals were performed (IQR 1-4) prior decision-making for ICS. ICS led in 90.2% (37/41) of cases to a final mTICI≥2b with significant improvement (p < 0.001) after the last retrieval attempt. The median NIHSS decreased (p = 0.178) from 7 (IQR 3.5-8) on admission to 2.5 (IQR 0-8.25) at discharge. ENI was observed in 47.4% (18/38). sICH occurred in 4.8% (2/41). Conclusion: ICS after failed thrombectomy appears to effectively improve recana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
(34 reference statements)
0
14
0
1
Order By: Relevance
“…We found that the meniscus sign was rare in the presence of underlying intracranial stenosis and is significantly associated with cardioembolic etiology, which is a known independent predictor of successful reperfusion [5]. In cohorts where the proportion of intracranial atherosclerotic stenosis is higher, such as in Asian stroke patients [15], a significant proportion of patients with large vessel occlusion and no meniscus sign will have an in situ thrombosis in an intracranial atherosclerotic plaque and/or stenosis, which may be associated with reduced efficacy of EVT [16]. Likewise, lower reperfusion rates are expected to be achieved in patients with basilar artery occlusion and no meniscus sign, because a high proportion of these patients will present a severe basilar artery stenosis, which is known to be responsible for 1/4 of basilar artery occlusion cases [17].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the meniscus sign was rare in the presence of underlying intracranial stenosis and is significantly associated with cardioembolic etiology, which is a known independent predictor of successful reperfusion [5]. In cohorts where the proportion of intracranial atherosclerotic stenosis is higher, such as in Asian stroke patients [15], a significant proportion of patients with large vessel occlusion and no meniscus sign will have an in situ thrombosis in an intracranial atherosclerotic plaque and/or stenosis, which may be associated with reduced efficacy of EVT [16]. Likewise, lower reperfusion rates are expected to be achieved in patients with basilar artery occlusion and no meniscus sign, because a high proportion of these patients will present a severe basilar artery stenosis, which is known to be responsible for 1/4 of basilar artery occlusion cases [17].…”
Section: Discussionmentioning
confidence: 99%
“…Adjusted for moderately severe stroke, early neurological improvement (ENI) was specified in a binary fashion as an improvement in NIHSS scores of at least 4 points or reaching 0 points. 21 Functional outcome was assessed with the modified Rankin Scale (mRS) score at the 90-day follow-up, with excellent functional outcome defined as an mRS score of 1 point or lower and favorable functional outcome as an mRS score of 2 points or lower. Mortality rates were assessed during hospitalization and at the 90-day follow-up.…”
Section: Clinical and Safety Outcomesmentioning
confidence: 99%
“…Adjusted for moderately severe stroke, early neurological improvement was defined in a binary fashion as an improvement in NIHSS scores of at least 4 points from baseline or reaching 0 points at discharge. 8 Functional outcome was assessed with the modified Rankin Scale (mRS) score with excellent functional outcome defined as an mRS score of 1 point or lower. The mRS was evaluated at 90-day follow-up by a physician or a trained and certified mRS nurse that were not directly involved in the patients' treatment.…”
Section: Clinical and Safety Outcomesmentioning
confidence: 99%